Comparative Analysis of the Properties of Acid-Base Indicator of Rose (Rosa setigera), Allamanda (Allamanda cathartica), and Hibiscus (Hibiscus rosa-sinensis) Flowers - Stanley I. R. Okoduwa; Lovina O. Mbora; Matthew E. Adu; Ameh A. Adeyi (Biochemistry Research International)
The need to develop effective alternative for synthetic indicators is the demand of present-day chemistry. The acid-base indicator properties of Rose (Rosa setigera), Allamanda (Allamanda cathartica), and Hibiscus (Hibiscus rosa-sinensis) flowers were examined. Colour pigments were extracted from the flowers via cold and solvent extraction using soxhlet extractor. The pH value of the extracts with wavelengths of absorption was determined using ultraviolet spectrophotometer. From the results obtained, all the extracts exhibited sharp contrast between their colours in acid and base. Their pH was found to be 5.5 for cold extract of Rose and 5.6 for solvent extraction, 5.24 for cold extract of a Hibiscus and 6.52 for solvent extraction, 5.35 for cold extract of Allamanda, and 5.45 for solvent extraction. The maximum wavelengths of absorption obtained for all the extract fall within the visible region of electromagnetic spectrum. These values are almost similar to that obtained from synthetic indicators. It is on these bases that we concluded that natural indicators could be an excellent replacement for synthetic indicators since they are cheap, readily available, simple to extract, not toxic, user and environmentally friendly.